2012
DOI: 10.1038/nchembio.937
|View full text |Cite
|
Sign up to set email alerts
|

Trp-tRNA synthetase bridges DNA-PKcs to PARP-1 to link IFN-γ and p53 signaling

Abstract: IFN-γ engenders strong anti-proliferative responses, in part through activation of p53. However, the long-known IFN-γ-dependent upregulation of human Trp-tRNA synthetase (TrpRS), a cytoplasmic enzyme that activates tryptophan to form Trp-AMP in the first step of protein synthesis, is unexplained. Here we report a nuclear complex of TrpRS with the catalytic subunit of DNA-dependent protein kinase (DNA-PKcs) and with poly (ADP-ribose) polymerase 1 (PARP-1), the major PARP in human cells. The IFN-γ-dependent poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
90
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 42 publications
4
90
1
Order By: Relevance
“…In addition to attaching Trp to its specific tRNA, which occurs mainly in the cytoplasm, WARS is involved in cellular signaling processes in the nucleus or in the extracellular space 21-24 . To investigate if Trp starvation affects WARS expression in specific cellular locations, we analyzed WARS protein expression in cytoplasmic and nuclear cell fractions (Figure 3F) as well as in cell supernatants (Figure 3G).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to attaching Trp to its specific tRNA, which occurs mainly in the cytoplasm, WARS is involved in cellular signaling processes in the nucleus or in the extracellular space 21-24 . To investigate if Trp starvation affects WARS expression in specific cellular locations, we analyzed WARS protein expression in cytoplasmic and nuclear cell fractions (Figure 3F) as well as in cell supernatants (Figure 3G).…”
Section: Resultsmentioning
confidence: 99%
“…A truncated version of WARS is secreted in response to IFNγ and elicits angiostatic effects 23 through inhibition of endothelial cell-cell junctions 24 . Upon infection, monocytes secrete full-length WARS, which induces phagocytosis and chemokine production in macrophages 21 . We therefore tested if the upregulation of WARS in response to Trp shortage also increases extracellular WARS protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these results suggested that regulation occurred due to negative feedback among TyrRS, PARP1, and SIRT1 under oxidative stress. In addition to their aminoacylation functions in protein synthesis, many aminoacyl-tRNA synthetases, including TyrRS, have been shown to take on multiple roles (41)(42)(43). Specifically, TyrRS was found to act as a sensor for oxidative stress after translocating to the nucleus, where it activates DNA damage repair genes that are downstream of E2F1 (7).…”
Section: Discussionmentioning
confidence: 99%
“…These domain additions are not needed for catalysis, but rather to endow the synthetases with functions beyond translation. These functions are associated with secreted, extracellular forms and with nuclear forms that are active in many different cell-signaling pathways (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). In addition, a recent study demonstrated that a novel domain, appended to SerRS at the time of the invertebrate to vertebrate transition, was essential for development of the closed vascular system (13).…”
mentioning
confidence: 99%